What can we learn about ELSA project implementation from the experiences of ELSAs and EPs? - Dalby, Eloise (2024)
Over the past two decades, the Emotional Literacy Support Assistant (ELSA) project has been delivered by educational psychologists (EPs) across the UK. Existing literature focuses on the efficacy of the ELSA project; however, less is understood about the factors that help the ELSA project to run. This study, therefore, sought to explore key stakeholders’ experiences of implementing the ELSA project.